Handbook of research on solar energy systems and technologies - Anwar, Sohail; Efstathiadis, Harry; Qazi, Salahuddin, 1938- (Engineering Science Reference/IGI Global, 2012)
"This reference serves as a one-stop resource for the latest information regarding different topical areas within solar energy, emphasizing the application of nanotechnology innovations to solar energy technologies, exploring current and future developments in third generation solar cells, and providing a detailed economic analysis of solar energy applications"--Provided by publisher.